2019
DOI: 10.1142/s2010007819500052
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Benefits of Climate Change in Switzerland

Abstract: Understanding the economic magnitude of climate change (CC) impacts is a prerequisite for developing adequate adaptation strategies. In Switzerland, despite new climate scenarios and impact studies, only few impacts have been monetized. Our objective is to assess costs and opportunities of CC for Switzerland by 2060, while enhancing the assessment methods. Using inputs from bottom-up impact studies, we simulate the economic consequences of climate scenarios in a computable general equilibrium (CGE) framework. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To value productivity losses associated with the reduced number of hot days, we assumed an average reduced worker productivity of 7% on a hot day (Vöhringer et al., 2017) given that productivity losses of 3% can be measured at temperatures of 26°C and productivity losses of 12% at 36°C (Bux, 2006). Although this approach does not consider the duration or intensity of exceedance of the temperature threshold, we believe this average estimate may underestimate the degree of productivity loss as the lower temperature range is not considered in our study (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…To value productivity losses associated with the reduced number of hot days, we assumed an average reduced worker productivity of 7% on a hot day (Vöhringer et al., 2017) given that productivity losses of 3% can be measured at temperatures of 26°C and productivity losses of 12% at 36°C (Bux, 2006). Although this approach does not consider the duration or intensity of exceedance of the temperature threshold, we believe this average estimate may underestimate the degree of productivity loss as the lower temperature range is not considered in our study (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a positive impact of natural disasters on the performance of the USA banks is reported in prior studies (Ewing et al , 2006). Furthermore, it is reported in prior studies that the financial/insurance sector may not be on the list of most impacted sectors by climate change, especially the extreme weather events (Vöhringer et al , 2019). It is concluded that natural disasters do not significantly impact the financial performance of the banks due to insurance of bank interests in the affected areas.…”
Section: Estimations and Findingsmentioning
confidence: 99%
“… ST. LUCIA SWEDEN SWITZERLAND Vöhringer, F.; Vielle, M.; Thurm, B.; Knoke, W.; Stocker, D.; Frehner, A.; Maire, S.; and Thalmann, P. Assessing the Impacts of Climate Change for Switzerland. Report Prepared for the Federal Office for the Environment: Bern, Switzerland, 2017 [111]. TAJIKISTAN THAILAND Thailand’s Climate Change and Health Country Profile [112].…”
Section: Table A1mentioning
confidence: 99%